Neurodevelopmental disorders: Risks of Zika virus during the first trimester of pregnancy. - Molnár, Z; Kennedy, S (Macmillan Publishers Limited, part of Springer Nature, 2016)
The ongoing Zika virus (ZIKV) epidemic in the Americas raises urgent questions about the risks of microcephaly in the children of ZIKV-infected mothers. New research into the 2013–2014 ZIKV outbreak in French Polynesia supports a link between maternal ZIKV infection during the first trimester of pregnancy and microcephaly.